CD71+ erythroid cells as a potential early biomarker for hemodynamic significant patent ductus arteriosus in preterm infants - Shin, Ju Ae; Lee, Jae Young; Shin, Jeongmin; Kim, Min Soo; Youn, Young-Ah; Kim, Joungok; Oh, Eun-Jee; Oh, Jin-Hee (Frontiers in Immunology, 2026)
IntroductionHemodynamically significant patent ductus arteriosus (hsPDA) in preterm infants is associated with increased mortality and morbidity. Early and accurate identification of infants at risk for PDA is critical for improving outcome. Perinatal inflammation is a known risk factor of PDA. CD71+ erythroid cells (CECs) are immature red blood cells with immunomodulatory roles and show variable abundance in preterm infants. We aimed to examine the proportion of CECs in preterm infants and investigate association with PDA.MethodsIn this prospective study, we evaluated the association between CEC levels and the development of hsPDA in a cohort of 108 preterm infants born before 37 weeks of gestation. CEC levels were quantified by flow cytometry within 12 hours of birth. The presence of hsPDA was assessed by echocardiography between days 3 and 7 after birth.ResultsCEC levels showed a significant inverse relationship with gestational age (CEC(%) = -0.4419 × Gestational Age + 18.7029, p<0.001). CEC levels were also inversely correlated with hemoglobin, red blood cells, white blood cells, and platelets (all p < 0.05). Infants who developed hsPDA had significantly higher CEC levels (7.5 ± 2.8% vs. 4.4 ± 1.7%, p < 0.0001), together with lower values of these hematologic parameters than infants without hsPDA. Multivariable logistic regression identified elevated CECs levels (odds ratio: 2.048, 95% CI: 1.326–3.162, p = 0.0012) and lower white blood cell count (odds ratio: 0.782, 95% CI: 0.620–0.986, p = 0.038) as independent predictors of hsPDA. Additionally, CECs levels were inversely correlated with hemoglobin, red blood cells, white blood cells, and platelets (p<0.05).DiscussionThese results suggest that early measurement of CEC levels can identify preterm infants at high risk for hsPDA prior to echocardiographic diagnosis. As a potential predictive biomarker, CECs may improve risk stratification and guide timely intervention, ultimately enhancing clinical outcomes. Further research is needed to elucidate the mechanisms linking CECs to hsPDA.